Shoe choice may affect fencing lunge attack performance - Wang, San-Tsai; Chang, Che-Chia; Chao, Te; Nicholls, Andrew; Tsai, Yung-Shen (Frontiers in Bioengineering and Biotechnology, 2024)
The purpose of this study was to investigate the differences in attack time and lower limb biomechanics when performing fencing lunge with fencing shoes (FS) and commonly used court shoes (CS). Additionally, the study aimed to evaluate whether fencing shoes with a heel cup (FSH) could reduce lower limb impact. Thirteen female collegiate fencers who had participated in national-level competitions were recruited for this study. Participants performed the lunge on a human-shaped target while wearing FS, FSH, or CS in a randomized order. Biomechanical data were collected using a 3D motion analysis system synchronized with a force plate. A signal light, and an accelerometer were attached to the target's head to initiate lunge movement and detect hit moment for calculating attack time. Attack time was significantly shorter when wearing FS (0.92 ± 0.05 seconds) and FSH (0.93 ± 0.07 seconds) compared to CS (0.96 ± 0.06 seconds). The maximum angular velocity of ankle plantarflexion in rear foot push-off phase was significantly slower when wearing FS and FSH than when wearing CS. The maximum knee posterior shear force, maximum knee flexion moment, and maximum ankle medial shear force during the front foot step phase were significantly greater when wearing FS than when wearing CS. These forces were significantly reduced or nearly significantly reduced when wearing FSH, and there were no significant differences compared to wearing CS. The maximum ankle medial shear force during the push-off phase in rear foot was the greatest when wearing FS but decreased significantly when using FSH. However, this force was still greater than when wearing CS. Wearing FS resulted in a higher loading rate (LR) on the front foot. This LR was reduced when a heel cup was used but still remained higher than when wearing CS. There were no significant differences in the forward extension of body, maximum ground reaction force, or center of pressure displacement during front foot step and rear foot push-off phases among the three shoe conditions. Wearing FS can enhance lunge performance, and the use of a heel cup can effectively reduce lower limb impact.